The Role of Sphingosine-1-Phosphate and Ceramide-1-Phosphate in Inflammation and Cancer. (15th November 2017) - Hait, Nitai C.; Maiti, Aparna
Abstract : Inflammation is part of our body's response to tissue injury and pathogens. It helps to recruit various immune cells to the site of inflammation and activates the production of mediators to mobilize systemic protective processes. However, chronic inflammation can increase the risk of diseases like cancer. Apart from cytokines and chemokines, lipid mediators, particularly sphingosine-1-phosphate (S1P) and ceramide-1-phosphate (C1P), contribute to inflammation and cancer. S1P is an important player in inflammation-associated colon cancer progression. On the other hand, C1P has been recognized to be involved in cancer cell growth, migration, survival, and inflammation. However, whether C1P is involved in inflammation-associated cancer is not yet established. In contrast, few studies have also suggested that S1P and C1P are involved in anti-inflammatory pathways regulated in certain cell types. Ceramide is the substrate for ceramide kinase (CERK) to yield C1P, and sphingosine is phosphorylated to S1P by sphingosine kinases (SphKs). Biological functions of sphingolipid metabolites have been studied extensively. Ceramide is associated with cell growth inhibition and enhancement of apoptosis while S1P and C1P are associated with enhancement of cell growth and survival. Altogether, S1P and C1P are important regulators of ceramide level and cell fate. This review focuses on S1P and C1P involvement in inflammation and cancer with emphasis on recent progress in the field.